THE THE EFFECT OF TRADE OPENNESS, EXPORTS AND IMPORTS OF AGRICULTURAL RAW MATERIALS ON GROSS DOMESTIC PRODUCT: A STUDY OF 8 ASEAN COUNTRIES (2018-2023) IN THE PERSPECTIVE OF ISLAMIC ECONOMIC - Dharmawan, Imam; Zuliansyah, A; Utamie, Zathu Restie (Ad-Deenar: Jurnal Ekonomi dan Bisnis Islam, 2025)
In Islamic economics, natural resources and human resources are factors in economic development. Gross Domestic Product (GDP) is a measuring tool to see and analyze a country's economic growth. This study aims to analyze the effect of trade openness, exports, and imports of agricultural raw materials on Gross Domestic Product (GDP) in 8 ASEAN countries from an Islamic economic perspective. This study uses panel data from 8 ASEAN countries in 2018-2023 obtained from the World Bank and the ASEAN Statistical Year Book with the saturated sampling method. Data analysis uses EViews10 software. The results of this study indicate that partially the export of agricultural raw materials has a negative effect on GDP, while trade openness and imports of agricultural raw materials have no effect on GDP in 8 ASEAN countries. The results of this study are expected to provide information and insight regarding GDP growth and the international trade sector in the ASEAN region and can contribute to the literature in Islamic economic studies.